2017
DOI: 10.1021/acsami.7b06296
|View full text |Cite
|
Sign up to set email alerts
|

Dentritic CuPtPd Catalyst for Enhanced Electrochemical Oxidation of Methanol

Abstract: The CuPtPd catalyst is designed and synthesized successfully via directly reducing metal ions. The composition, morphology, and structure of the as-prepared CuPtPd nanohybrids are characterized by scanning electron microscopy and transmission electron microscopy, energy-dispersive spectrometry, selected-area electron diffraction, X-ray diffraction, and inductively coupled plasma atomic emission spectrometry. By comparison of the electrocatalytic properties of the ternary CuPtPd catalyst with bimetallic catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
(55 reference statements)
0
38
0
Order By: Relevance
“…Direct methanol fuel cells (DMFCs) are of great interest because of their high efficiency, low operation temperature, and zero emissions, leading to wide applications in portable and mobile devices . Electrocatalysts are essential components in DMFCs due to the sluggish kinetics and short duration of the anodic reaction, methanol oxidation reaction (MOR) . Most of the electrocatalysts developed have been limited to Pt and its alloys, which are still considered to be the best electrocatalysts for MOR .…”
Section: Introductionmentioning
confidence: 99%
“…Direct methanol fuel cells (DMFCs) are of great interest because of their high efficiency, low operation temperature, and zero emissions, leading to wide applications in portable and mobile devices . Electrocatalysts are essential components in DMFCs due to the sluggish kinetics and short duration of the anodic reaction, methanol oxidation reaction (MOR) . Most of the electrocatalysts developed have been limited to Pt and its alloys, which are still considered to be the best electrocatalysts for MOR .…”
Section: Introductionmentioning
confidence: 99%
“…In our case, J f /J b for the 3.8 ± 1.6 and 9.2 ± 2 nm NWs was found to be 3.2 and 1.7, respectively. While the PVP layer has been reported to affect the accessibility of alcohols to the catalyst's surface, it has been widely used on a range of electro-catalysts and does not significantly inhibit their overall performance [77][78][79][80]. Compared with other catalysts (Table 1), our NWs, particularly the 3.8 nm diameter NWs, have a remarkable catalytic performance with a poison resistance comparable to many of the state-of-the-art noble metal catalysts.…”
Section: Electro-oxidation Of Ethylene Glycol Using Selected Auag 1d mentioning
confidence: 94%
“…[25,[31][32][33][34][35] The reactivity of Li anode has also been theoretically confirmed. [36][37][38] It has been found that the electrolyte salts ( Figure 3a) [29] and additives ( Figure 3b) [28] are repeatedly reduced/precipitated on the Li surface from solution. [39][40][41][42] Some of the aprotic salts, such as LiBF 4 , LiPF 6 , LiN(SO 2 CF 3 ) 2 , and LiSO 3 CF 3 are moisture sensitive and produce HF as the hydrolysis product due to the presence of trace moisture in the electrolyte solvents, which immediately react with Li metal anode until the electrolyte is vanished.…”
Section: Reactivity Of LI Metalmentioning
confidence: 99%
“…Extensive research has been done over the past 40 years to understand the structure and composition of SEI film. [30,37,38,58,60,72,[74][75][76][77] [14,25,29,30,76] The composition of SEI can be correlated with the reactivity of the electrolyte components and solvated electrons (e − solv ). [66,75,78,79] For instance, BF − 4 and ClO − 4 are significantly less reactive toward e − solv , and LiCl and boron (B 0 ) are rarely found in the SEI.…”
Section: The Sei On a LI Metal Anodementioning
confidence: 99%
See 1 more Smart Citation